Encouraging Environmentally Sustainable Growth in Austria - Høj, Jens (OECD Economics Department Working Papers, 2002)
This document analyses the economic impacts of selected environmental policies in Austria with an emphasis on the use of economic instruments and incentives versus command-and-control measures. An important theme in a federation like the Austrian is the institutional complexity involved in many aspects of environmental policy, requiring a high degree of co-ordination between various layers of government, which could be furthered by a coherent ex ante and ex post evaluation system. Such a system could also be useful in the setting of abatement objectives and minimizing their associated cost. Greater use of properly designed instruments, examples being a unified taxation of fuels and the introduction of a CO2 tax, would improve the cost-effectiveness of policies to reach Austria's ambitious CO2 emission reduction target. This would particularly be the case if economic instruments replace the widespread use of subsidies and command-and-control type measures. Such measures are found to ...